The comparison of the lactation and milk yield and composition of selected breeds of sheep and goats - Ferro, M. M. (Transl Anim Sci, 2017)
The objective of this study was to characterize the milk yield (MY) and milk composition of relevant sheep and goat breeds raised around the world to be used with nutrition models for diet formulation and nutrient balancing. A 2-step approach was used. First, a database developed by the Food and Agriculture Organization was used to identify relevant breeds (i.e., frequently raised) by comparing the occurrence of transboundary breed names across countries. We selected transboundary breeds that occurred more than 3 times and other relevant breeds obtained from the specialized literature that had milk production information (e.g., MY, days in milk, and milk fat, protein, and lactose). The majority of sheep breeds were classified as nondairy (76%) because they lacked milk production information. Karakul and Merino accounted for up to 2.4% of sheep breeds raised around the world, whereas the other individual breeds accounted for less than 1%. In contrast, nondairy breeds of goats accounted for 46.3% and of the remaining 53.7%, Saanen, Boer, Anglo-Nubian, Toggenburg, and Alpine accounted for 6.5, 5, 4.4, 4, and 3%, respectively, of the transboundary breeds. Second, a database compiled from published studies for the selected sheep (n = 65) and goats (n = 78) breeds were analyzed using a random coefficients model (studies and treatments within studies as random effects). For sheep breeds, the average and SD were 1.1 ± 0.3 kg/d for MY, 6.9 ± 1% for milk fat, 5.4 ± 0.4% for milk protein, 5 ± 0.3% for milk lactose, 17.7 ± 1.4% for milk total solids, and 1,073 ± 91 kcal/kg of milk energy. Lacaune had the greatest MY compared to Comisana and Tsigai (1.65 versus 0.83 and 0.62 kg/d; respectively, P < 0.05), but milk components were not different among breeds. For goats breeds, the average and SD across breeds were 1.7 ± 0.6 kg/d for MY, 4.2 ± 0.9% for milk fat, 3.3 ± 0.4% for milk protein, 4.4 ± 0.4% for milk lactose, 12.7 ± 1.1% for milk total solids, and 750 ± 75 kcal/kg of milk energy. Alpine had similar MY to Saanen (2.66 versus 2.55 kg/d, respectively; P > 0.05), but greater (P < 0.05) than other breeds. The Boer breed had the greatest milk fat, protein, lactose, and total solids than several other breeds, leading to the greatest milk energy content (907 kcal/kg). Because there are many factors that can alter MY and milk composition, averages provided in this study serve as guidelines, and nutritionists must obtain observed values when using nutrition models.